Oral cholera vaccine coverage evaluation survey: Forcibly Displaced Myanmar Nationals and host community in Cox's Bazar, Bangladesh - Qayum, Md. Omar; Billah, Mallick Masum; Sarker, Mohammad Ferdous Rahman; Alamgir, A. S. M.; Nurunnahar, Mehejabin; Khan, Manjur Hossain; Salim Uzzaman, M.; Henderson, Alden; Shirin, Tahmina; Flora, Meerjady Sabrina (Frontiers in Public Health, 2023)
Introduction Cholera remains a significant public health concern in many parts of the world, particularly in areas with poor sanitation and hygiene. Bangladesh and other impoverished nations have been severely affected by cholera outbreaks, especially in areas with a high population density. In order to mitigate the spread of cholera, oral cholera vaccines (OCVs) are recommended as a prophylactic measure. In May 2018, 775,666 of the Forcibly Displaced Myanmar Nationals (FDMN) in the registered and makeshift camps and 103,605 of the residents in the host community received two doses of OCV ShancholTM in Cox's Bazar, Bangladesh, because the conditions in the area favored the transmission of cholera and other waterborne diseases. This study aimed to assess the coverage of OCV among the FDMN and the host community in Cox's Bazar. Methods In August 2018, we enrolled 4,240 respondents for this study following the “World Health Organization (WHO) Vaccination Coverage Cluster Surveys: Reference Manual (2018).” The coverage survey was conducted with three strata of the population: the host community from the Teknaf Upazila, the registered camp, and the makeshift camp from the Ukhia Upazila. We collected information regarding OCV coverage, demographic characteristics, and knowledge and behaviors of people toward the vaccine. The data were analyzed using descriptive statistics. Results According to our study, the overall OCV coverage was 85%, with 68% in the host community, 91% in the registered camp, and 98% in the makeshift camp. The lower coverage in the host community was due to residents unaware of the vaccination campaign, the unavailability of vaccines, and unaware where to go for vaccination. Discussion Our findings demonstrate that the OCV campaign in the FDMN camps was successful, reaching over 90% coverage, while coverage in the host community was much lower. In order to make sure that OCV vaccination efforts are reaching the target population and having the desired impact, our study emphasizes the need to inform the target population of when and where to get vaccinated.